Access to family planning services and associated factors among young people in Lira city northern Uganda - Eustes Kigongo; Raymond Tumwesigye; Maxson Kenneth Anyolitho; Marvin Musinguzi; Gad Kwizera; Everlyne Achan; Caroline Kambugu Nabasirye; Samson Udho; Amir Kabunga; Bernard Omech (BMC, 2024)
Abstract Background Access to family planning services among young people is crucial for reproductive health. This study explores the access and associated factors among young people in Lira City, Northern Uganda. Methods and materials A mixed-methods study was conducted in March to April 2022. Quantitative data were collected using a structured questionnaire from 553 participants aged 15-24 years. Qualitative data were obtained through in-depth interviews and focus group discussions. Data analysis included univariate, bivariate, and multivariate analyses for quantitative data, while interpretative phenomenological analysis was used for qualitative data. Results Overall, 31.7% of the respondents had a good perceived access to family planning services, with 64.6% reporting perceived availability of FP methods. Challenges included lack of privacy (57.7%), fear of mistreatment (77.2%), and decision-making difficulties (66.2%). Among females, good perceived access to FP services was less likely among urban residents (AOR: 0.22, 95% CI: 0.09-0.53), Christian respondents (AOR: 0.51, 95% CI: 0.01-0.36), Muslim respondents (AOR: 0.07, 95% CI: 0.01-0.55) and respondents with poor attitude to FP services (AOR: 0.39, 95% CI: 0.24-0.64), but more likely among respondents with a sexual a partner (AOR: 4.48, 95% CI: 2.60-7.75). Among males, good perceived access to FP services was less likely among respondents living with parents (AOR: 0.19, 95% CI: 0.05-0.67) but more likely among respondents with good knowledge of FP services (AOR: 2.28, 95% CI: 1.02-5.32). Qualitative findings showed that three themes emerged; knowledge of family planning methods, beliefs about youth contraception and, friendliness of family planning services. Conclusion The study revealed a substantial gap in perceived access to family planning services among young people in Lira City. Barriers include privacy concerns, fear of mistreatment, and decision-making difficulties. Tailored interventions addressing urban access, religious beliefs for females, and knowledge enhancement for males are essential. Positive aspects like diverse FP methods and physical accessibility provide a foundation for targeted interventions. Youth-friendly services, comprehensive sexual education, and further research are emphasized for a nuanced understanding and effective interventions in Northern Uganda.